Bodies of knowledge in ancient Mesopotamia: the diviners of Late Bronze Age Emar and their tablet collection - Rutz, Matthew (Ancient magic and divination, 2013)
In Bodies of Knowledge in Ancient Mesopotamia Matthew Rutz investigates how libraries and archives can be used to study ancient diviners, an approach illustrated using one family's cuneiform tablet collection from Emar on the Syrian Euphrates (ca. 1375-1175 BCE)